The use of different organisational forms in ELT - Osmíková, Alena (Univerzita Pardubice, 2011)
This thesis focuses on the use of different organisational forms in English language teaching. The theoretical part, which is the basis for the practical part, specifies organisational forms - frontal teaching, individual work, group work and pair work - in terms of advantages and disadvantages, roles of the teacher and learners, class management and activities appropriate for each organisational form. The practical part describes research procedure and outcomes. The main aim of the research is to determine the purposes and frequency of using different organisational forms in English language teaching.
Využití různých organizačních forem ve výuce anglického jazyka
Keywords: organizační formy; frontální vyučování; individuální práce žáků; skupinové vyučování; vyučování ve dvojicích; výuka anglického jazyka; organisational forms; frontal teaching; individual work; group work; pair work; teaching English language